Covid-19 pandemic and effect of containment measures in the Peruvian population: A SIR mathematical modeling - Espinola-Sánchez, Marcos (2020)
Introduction: The evolution of the COVID-19 pandemic varies in each population; it has been complicating health systems worldwide. Objective: to analyze the evolution of the Covid-19 pandemic, estimating the effect of the containment measures practiced in Peru. Material and Method: The SIR epidemiological mathematical modeling was applied, estimating the COVID-19 evolution in our population. Data analysis was performed following the SIR mathematical model with defined ordinary differential equations to simulate epidemiological behavior; and it was executed in the RStudio programming language. Results: Containment measures decreased the propagation rate, reducing 30% of infected cases until the peak day of infection; however, it is still above the effective reproductive number to control the epidemic and it shows an erratic trend, the result of government actions being 61% in the practice of containment measures. Conclusions: Containment measures are necessary if strategies are considered to make their role effective in our population.